Respuesta :

Step-by-step explanation:

How I figured this out is kind of plug in play with a bit of algebra, you want to get it to y = mx + b so to do that, you first need to set up your equation like (y - y1) = m(x - x1)

Plug in what you know:

(y - 4) = 1/2(x + 2)  (notice I changed the x- x1 to x + x1 because x1 in this is a negative and subtracting a negative is the same as adding)

Then figure out what you don't know:

Distribute 1/2 to x and -2

(y - 4) = 1/2x -1

add 4 on both sides to leave y by itself

y = 4.5x + 3

Therefore your answer should be y = 4.5x + 3

Let me know if I got it wrong please

Hope this helps! <3